Korupsi dalam Perspektif Hadis Imam Bukhari - Moh Hilmi Badrut Tamam; Andris Nurita (El Nubuwwah Jurnal Studi Hadis, 2023)
Corrupt behavior has developed into a serious and destructive problem throughout the world, affecting many countries, including Indonesia. In the hadith of the Prophet Muhammad SAW, corrupt behavior is described as narrated by Sahih Bukhari number 3196. This hadith discusses corruption in the form of taking other people's rights and this hadith is one of the hadiths that can help people avoid corrupt behavior. This research uses qualitative methods based on library research, books, journals, and scriptures. This research is based on the hadith of the Prophet Muhammad SAW and strengthened by the thoughts of Yusuf al-Qardhawi. This research aims to find out how the hadith narrated by Imam Bukhari No. 3196 regarding corruption is understood according to Yusuf al-Qaradawi thoughts, analyzing the factors influencing corruption and how efforts are made to prevent corruption based on hadith analysis. With this, this research reveals that this hadith is an authentic hadith which has no defects and according to Yusuf al-Qaradawi the hadith is not only interpreted textually but also by looking at the context. Then, the corruption that occurs in Indonesia is largely influenced by human resources who have minimal understanding of corruption, lack of economics, and misappropriation of responsibility. Lastly, prevention efforts that can be carried out include optimizing the public's moral and ethical education regarding corruption awareness and strengthening the law regarding corruption in Indonesia.